2015
DOI: 10.1080/15332985.2014.916646
|View full text |Cite
|
Sign up to set email alerts
|

Negative Appraisal and Traumatic Stress Symptoms in Community Clients With Serious Mental Illness

Abstract: We examined the relationship between negative appraisal and posttraumatic stress disorder (PTSD) symptoms among adults diagnosed with severe mental illness (SMI). It was hypothesized that negative appraisals of the self, the world, and self-blame would have a positive and significant association with traumatic stress symptoms in a clinical sample of community clients diagnosed with an Axis I primary diagnosis of either severe major mood disorder or schizophrenia-spectrum disorder when controlling for gender, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Also, individual growth curve models based upon the data used in the current study showed no differences for this population in overall sense of threat (Gelkopf et al., in press). Those results are not in line with previous literature (e.g., Sherrer et al., ).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Also, individual growth curve models based upon the data used in the current study showed no differences for this population in overall sense of threat (Gelkopf et al., in press). Those results are not in line with previous literature (e.g., Sherrer et al., ).…”
Section: Discussioncontrasting
confidence: 96%
“…The higher PTSS rates in women might be due to increased peritraumatic reactions, and increased appraisal of events as threatening (Irish et al., ; McLean & Anderson, ; Olff, Langeland, Draijer, & Gersons, ). People with SMI, particularly psychotic disorders (Gaynor, Ward, Garety, & Peters, ), and anxiety disorders (Stapinski, Abbott, & Rapee, ), are also more prone to appraise events or situations as threatening or dangerous (Sherrer, ; Sherrer, Shen, & O'Hare, ). However, the link between exposure level, sense of threat, and peritraumatic stress symptoms within these populations still needs clarification.…”
mentioning
confidence: 99%
“…It may also be that the key element linking physiological and cognitive responses to stress is the psychological appraisal of the experience itself. For example, when understanding the effects of trauma on psychopathological outcomes, cognitive theorists suggest it is not the event itself which matters most but rather the interpretation and attributions formed by the individual after the traumatic experience (Sherrer, Shen, & O'Hare, 2015). Appraisals of circumstances may also be influenced by individual differences such as personality factors.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, biased appraisal due to impaired cognitive or emotional mechanisms may enhance negative emotional reactions to stress (Fox, Cahill, & Zougkou, 2010). Such biased appraisal is often found in people with mental illness (Fox et al, 2010; Sherrer, Shen, & O'Hare, 2015), who indeed generally show heightened emotional reactivity to stress (Myin‐Germeys et al, 2018).…”
Section: Introductionmentioning
confidence: 99%